Development and evaluation of teak (Tectona grandis L.f.) taper equations in northern Thailand - Warner, Andrew J.; Jamroenprucksa, Monton; Puangchit, Ladawan (Agriculture and Natural Resources, 2016)
Taper refers to the general decrease in the regular outline of a solid body from its base to its tip. Taper models are used to estimate the volume and value of wood products from harvesting trees. Teak (Tectona grandis L.f.) is highly valued as one of the world's most preferred timbers and a teak taper equation is required to inform optimal harvesting strategies given the limited plantation resource available in Thailand. Teak taper equations were developed and evaluated based on 331 sample trees collected in 2014 from eight plantations in northern Thailand aged from 10 to 46 yr using two taper model formulationsdthe Kozak variable-exponent taper model and the Goodwin cubic polynomial model comprising hyperbolic and parabolic terms. Variants based on both model types were fitted using nonlinear regression analysis with diameter at breast height, total tree height and height of girth measurement as the independent variables to estimate diameter underbark at the nominated height. Goodness-of-fit and leave-one-out cross validation with lack-of-fit statistical testing combined with extensive graphical analysis of residuals were used to select the best model. A Goodwin model variant (named FIO-teak1 as the first plantation teak taper model known to be published in Thailand) provided the best estimates of volume and diameter underbark. A simple case study confirmed that FIO-teak1 in combination with the Farm Forestry Toolbox software package could assist teak plantation managers in decision making associated with optimizing log grade value based on standing tree inventory data.